The evaluation of speed skating helmet performance through peak linear and rotational accelerations - Karton, C.; Rousseau, P.; Vassilyadi, M.; Hoshizaki, T. B. (British Journal of Sports Medicine, 2014)
Objective: Like many sports involving high speeds and body contact, head injuries are a concern for short track speed skating athletes and coaches. While the mandatory use of helmets has managed to nearly eliminate catastrophic head injuries such as skull fractures and cerebral haemorrhages, they may not be as effective at reducing the risk of a concussion. The purpose of this study was to evaluate the performance characteristics of speed skating helmets with respect to managing peak linear and peak rotational acceleration, and to compare their performance against other types of helmets commonly worn within the speed skating sport. Materials and methods: Commercially available speed skating, bicycle and ice hockey helmets were evaluated using a three-impact condition test protocol at an impact velocity of 4 m/s. Results: and discussion Two speed skating helmet models yielded mean peak linear accelerations at a low-estimated probability range for sustaining a concussion for all three impact conditions. Conversely, the resulting mean peak rotational acceleration values were all found close to the high end of a probability range for sustaining a concussion. A similar tendency was observed for the bicycle and ice hockey helmets under the same impact conditions. Conclusion: Speed skating helmets may not be as effective at managing rotational acceleration and therefore may not successfully protect the user against risks associated with concussion injuries.